2018
DOI: 10.1098/rsos.172125
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic history of enigmatic pygmy perches: implications for biogeography, taxonomy and conservation

Abstract: Pygmy perches (Percichthyidae) are a group of poorly dispersing freshwater fishes that have a puzzling biogeographic disjunction across southern Australia. Current understanding of pygmy perch phylogenetic relationships suggests past east–west migrations across a vast expanse of now arid habitat in central southern Australia, a region lacking contemporary rivers. Pygmy perches also represent a threatened group with confusing taxonomy and potentially cryptic species diversity. Here, we present the first study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(71 citation statements)
references
References 96 publications
(161 reference statements)
3
65
0
3
Order By: Relevance
“…22) reveal that under the names Percilia gillissi and P. irwini are other cryptic species. Similar results have been published concerning Macquaria (Musyl, Keenan, 1992;Beheregaray et al, 2017), Gadopsis (Hammer et al, 2014;Unmack et al, 2017), and Nannoperca (Unmack et al, 2011;Buckley et al, 2018). Consequently, there is much more work needed to clarify the taxonomy of the South American and Australian percichthyids and perciliids.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…22) reveal that under the names Percilia gillissi and P. irwini are other cryptic species. Similar results have been published concerning Macquaria (Musyl, Keenan, 1992;Beheregaray et al, 2017), Gadopsis (Hammer et al, 2014;Unmack et al, 2017), and Nannoperca (Unmack et al, 2011;Buckley et al, 2018). Consequently, there is much more work needed to clarify the taxonomy of the South American and Australian percichthyids and perciliids.…”
Section: Discussionsupporting
confidence: 70%
“…Recent molecular studies suggested that there are cryptic species within Nannoperca (Unmack et al, 2011;. A phylogenomic study published recently confirmed the paraphyletic nature of N. vittata, revealing two new cryptic lineages within the species and recognizing informally the existence of N. 'flindersi' (Buckley et al, 2018). However, Buckley et al (2018) emphasized that a more comprehensive sampling may reveal the full geographic range of the delimited species, including morphological and ecological characters for establishing species boundaries.…”
Section: E180102[13]mentioning
confidence: 99%
See 1 more Smart Citation
“…because they have no close phylogenetic relatives; because they are relatively young lineages; and/or because they have sister lineages elsewhere in southern Victoria). These lineages include the phylogenetically highly divergent Ewens pygmy perch Nannoperca variegata (Buckley et al, ; Unmack, Hammer, Adams, & Dowling, ), an apparent relict species estimated to have diverged from its closest living relatives (including Murray‐Darling populations of Nannoperca australis ) some 15–20 mya (Buckley et al, ; although it is possible that a more recent sister lineage has gone extinct). Additional examples of SWV freshwater diversity include the western swamp crayfish ( Gramastacus insolitus ) which is restricted to southwestern Victoria and south‐eastern South Australia (Zeidler & Adams, ).…”
Section: Southeast Australian Freshwater Phylogeogeographymentioning
confidence: 99%
“…Mitogenomes enable support to complex situations in which specific status was not previously assessed and/or ambiguous (e.g., Beheregaray et al, 2017;Buckley et al, 2018), and also provide support for a more integrative and corroborative taxonomy in which morphology and molecular species delineation have been shown to match (Pedraza-Marrón et al, 2019) or not (Vernygora et al, 2018).…”
Section: In the Meantime…mentioning
confidence: 98%